Why Do States Extend Rights to Immigrants? Institutional Settings and Historical Legacies Across 44 Countries Worldwide - Ruud Koopmans; Ines Michalowski (Comparative Political Studies, 2017)
In this article, we first test theories on immigrant rights across 29 countries from Europe, Africa, the Middle East, East Asia, Oceania, and the Americas, using our Indicators of Citizenship Rights for Immigrants (ICRI) data set. We focus on trajectories of nationhood and current institutional features to explain cross-national difference. We find that former colonial powers, former colonies that developed as settler countries, as well as democracies have been more likely to extend rights to immigrants. Strikingly, once we account for involvement in colonialism, we find no difference between supposedly “civic-nationalist” early nation-states and supposedly “ethnic-nationalist” latecomer nations, refuting a widely held belief in the literature on citizenship. We find no effect of a country's degree of political globalization. We replicate these findings on a sample of 35 mainly European countries, using the migrant Integration Policy Index (MIPEX).
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; migration; globalization; citizenship rights; ethnic versus civic nationalism